Monetary policy and bank equity values in a time of low interest rates - Miguel Ampudia; Skander van den Heuvel (European Central Bank (ECB), 2018)
This paper examines the effects of monetary policy on the equity values of European banks. We identify monetary policy shocks by looking at changes in the EONIA one-month and two-year swap contract rates during narrow windows around the press statements and press conferences announcing monetary policy actions taken by the ECB. We find that an unexpected decrease of 25 basis points on the short-term policy rate increases banks' stock prices by about 1% on average. These effects vary substantially over time; in particular, they were stronger during the crisis period and reversed during the recent period with low and even negative interest rates. That is, with rates close to or below zero, further interest rate cuts became detrimental for banks' equity values. The composition of banks' balance sheets is important in order to understand these effects. In particular, the change in sensitivity to interest rate surprises as rates drop to low and negative levels is much more pronounced for banks with a high reliance on deposit funding, compared to other banks. We argue that this pattern can be explained by a reluctance of banks to pay negative interest rates on retail deposits.
Keywords: E52; E58; G21; 330; monetary policy; negative rates; bank profitability; ECB